No walls of stone : an anthology of literature by deaf and hard of hearing writers - Jepson, Jill Christine, 1950- (Gallaudet University Press, 1992)
A collection of literature by poets, novelists, short-story writers, playwrights, journalists, and essayists, all of whom live the deaf experience.